Local production of essential oil - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
s In response to increasing demands from Europe and the USA, Asian and African countries are now increasing their production of crops such as basil, geranium, and mint for oil extraction. Growing and preparing essential oils is labour-intensive,...